Lung cancer cell derived sEVs enhance the metastasis of non-small cell lung cancer via SNHG12/miR-326/SLC7A11 axis - Yiqian Liu; Ling Zhang; Jian Wang; Jiali Xu; Jing Xu; Mengyan Xie; Rong Wang (Cancer Biology & Therapy)
Abnormally expressed long non-coding (lnc)RNAs are closely associated with the pathogenesis of non-small cell lung cancer (NSCLC); thus, the present study aimed to investigate the potential role of SNHG12 in NSCLC. Transmission electron microscopy and nanoparticle tracking analysis were conducted to verify NSCLC cell-derived small extracellular vesicles (sEVs). MicroRNA (miRNA/miR) and mRNA expression levels were determined using reverse transcription-quantitative PCR, while protein expression levels were determined using western blot analysis and immunofluorescence. In addition, potential binding sites between miR-326 and SNHG12/SLC7A11 were verified using a dual-luciferase reporter assay. Cell behavior was detected using flow cytometry, colony formation, wound healing and Transwell assays, and xenograft experiments were conducted to confirm the roles of SNHG12 in NSCLC. H&E staining was used for histological analysis, and each experiment was repeated three times. Results of the present study demonstrated that NSCLC-derived SNHG12 promoted type-2 tumor-associated macrophage (TAM2) polarization. However, the decrease of SNHG12 expression in EVs reduced TAM2 polarization, weakened NSCLC cell proliferation, migration and invasion, and promoted tumor cell ferroptosis. Moreover, results of the present study revealed that SNHG12 knockdown markedly suppressed tumor growth and the metastasis of NSCLC. In addition, SNHG12 upregulated SLC7A11 expression via binding to miR-326. Overexpressed SLC7A11 promoted tumor aggressiveness and suppressed the ferroptosis of NSCLC cells. Collectively, results of the present study revealed that SNHG12 suppressed ferroptosis and promoted the metastasis of NSCLC, further demonstrating that high SNHG12 expression levels may be indicative of poor clinical outcomes for patients with NSCLC. Thus, the present study highlighted that the SNHG12/miR-326/SLC7A11 axis may exhibit potential as a novel target for the treatment of NSCLC.